Assessment of long-term remission in lupus nephritis patients: a retrospective analysis over 30 years. (27th February 2015) - Fernandes das Neves, Marisa; Irlapati, Rajendra Vara Prasad; Isenberg, David
Abstract : Objective. To review the likelihood of very long-term remission in patients with biopsy-proven LN attempting to identify good prognostic features. Methods. We reviewed patients with LN whose renal biopsies showed World Health Organization (WHO) classes III, IV and V and who had a follow-up of at least 5 years between 1973 and 2008. We analysed demographic, clinical, laboratory and therapeutic parameters comparing those patients with (group A) and without (group B) 5 year remission. Results. Of 191 LN patients followed, 105 patients met the strict inclusion criteria. Ninety-five patients were female. Mean age at diagnosis of lupus was 24.1 years (s.d. 10.7). ean age at diagnosis of LN was 28.4 years (s.d. 11.3). The mean duration of follow-up was 13.7 years (s.d. 14.1). Forty (38%) patients achieved 5 year remission, of whom 17 (16.2%) had remission for ≥15 years. The incidence of flares per year from 5 to 15 years was 7.9%; however, no flares were observed after 15 years of remission. The only distinguishing feature found in this study was the association of WHO class IV on kidney biopsy with LN progression ( P = 0.03). Conclusion. Renal histology with WHO class IV predicted a poor long-term remission rate. Age, sex, ethnicity, serological parameters and treatment received did not predict long-term remission. Renal flares can occur up to 15 years after a patient has gone into remission.